1989
DOI: 10.1128/jb.171.5.2666-2672.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of nitrate assimilation in Klebsiella pneumoniae M5al

Abstract: We isolated Mu d11734 insertion mutants of Klebsiella pneumoniae that were unable to assimilate nitrate or nitrite as the sole nitrogen source during aerobic growth (Nas-phenotype). The mutants were not altered in respiratory (anaerobic) nitrate and nitrite reduction or in general nitrogen control. The mutations were linked and thus defined a single locus (nas) containing genes required for nitrate assimilation. ,I-Galactosidase synthesis in nas+l¢(nas-lacZ) merodiploid strains was induced by nitrate or nitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…4). Nitrate induces transcription of nitrate assimilation genes in higher plants (6), fungi (6,24), and bacteria (4,10,28), and nitrite has been shown to be an alternative inducer in the fungus Aspergillus nidulans (13,36) and the bacterium Klebsiella pneumoniae (4,10). The present results revealed that nitrate and nitrite activate the nitrate assimilation genes in the cyanobacteria Synechococcus sp.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…4). Nitrate induces transcription of nitrate assimilation genes in higher plants (6), fungi (6,24), and bacteria (4,10,28), and nitrite has been shown to be an alternative inducer in the fungus Aspergillus nidulans (13,36) and the bacterium Klebsiella pneumoniae (4,10). The present results revealed that nitrate and nitrite activate the nitrate assimilation genes in the cyanobacteria Synechococcus sp.…”
supporting
confidence: 48%
“…It is transported into the cells by an active transport system and reduced to ammonium by the sequential action of nitrate reductase (NR) and nitrite reductase (NiR) prior to fixation into the amide nitrogen of glutamine (Gln). As in other microorganisms capable of nitrate assimilation (3,4,6,8,19,24), expression of the nitrate assimilation system is inhibited by ammonium (12). In the unicellular non-nitrogen-fixing cyanobacterium Synechococcus sp.…”
mentioning
confidence: 99%
“…Further characterization of this translational coupling identified a secondary structure which prevents independent translation of nifA, making it dependent on full translation of nifL. (6) and the nifLA duplication-bearing strains SE1004 and SE1005 (as VJSK014Rif, but pIZ287::nifLA and pIZ288::nifLA, respectively; for details of construction, see below).…”
mentioning
confidence: 99%
“…The significance of this constitutivity remains unknown. Cali et al showed clearly that the K. pneumoniae nas-lac fusions were regulated by the NTR system at the level of gene expression (2). Macaluso et al (5) showed that NAS formation in K. aerogenes similarly required the NTR system (but not the nitrogen assimilation control system) for nitrogen regulation.…”
mentioning
confidence: 99%
“…Cali et al have recently considered the genetic regulation of NAS in Klebsiella pneumoniae (oxytoca) M5al (2). They overcame the instability of NAS in the assay mixture by isolating fusions of the lacZ gene to nas promoters and assaying P-galactosidase instead of NAS.…”
mentioning
confidence: 99%